Rahmah El Yunusiah: Pioneer of Islamic Women Education in Indonesia, 1900 â 1960âs - Alfian, Magdalia (TAWARIKH, 2012)
ABSTRACT: Rahmah El Yunusiah is one of the figures and fighters for the Indonesian women. Rahmah El Yunusiah (REY) was born on December 20th, 1900 in the city of Padang Panjang, West Sumatra District, a small town in the western part of Indonesia. In the history of Indonesia, REY is known as the founder of the âPerguruan Diniyah Putriâ or Ladies Religion School in Padang Panjang which is quite famous. The school still exists up to the present and has produced thousands of alumni who are scattered in various regions in Indonesia, Singapore, and Malaysia. The success of REY in managing the school was apparently supported by several things, among others, the Minangkabau matrilineal kinship system. Women as mothers or âBundo Kanduangâ have a kinship system and the freedom to carry out their ideals. With the properties owned by REY, she successfully managed to establish the school. Until her death in 1969, REY still remained faithful to maintain the existence of the school she started. Currently, the Ladies Religion School has various levels of education starting from kindergarten to university.KEY WORDS: Rahmah El Yunusiah, position and roles the women, Minangkabau matrilineal system, and Islamic education institution.About the Author: Dr. Magdalia Alfian is a Senior Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia. She can be contacted via her e-mail address at: magdalia_alf10@yahoo.comHow to cite this article? Alfian, Magdalia. (2012). âRahmah El Yunusiah: Pioneer of Islamic Women Education in Indonesia, 1900 â 1960âsâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.55-66. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 28, 2012); Revised (September 30, 2012); and Published (October 28, 2012).